The Effect of Price and Trust on Purchasing Decisions with Interest in Buying Online Shopping as an Intervening Variable (Study on ERIZEN.ID Online Shop) - Rini Widya Oktaviani; Adietya Arie Hetami (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted aiming to find out how the price and trust influences purchasing decisions with buying interest online as an intervening variable. By using the number of samples research as many as 100 respondents, as well as sampling conducted using non-probability sampling with a purposive sampling approach. Data collection using a questionnaire in the form of google form. Testing data analysis with instrument test method, classic assumption test, linear regression analysis multiplex, hypothesis testing and path analysis. The results of this study indicate that: (1) prices affect interest buy online shopping; (2) trust has an effect on buying interest on line; (3) price and trust have a simultaneous effect on purchase intention online shopping; (4) prices affect purchasing decisions; (5) trust influences purchasing decisions; (6) price and trust has a simultaneous effect on purchasing decisions; (7) interest buying online shopping has an effect on purchasing decisions; (8) prices through interest in buying online shopping has a direct effect on purchasing decisions; (9) Trust through interest in buying online shopping has a direct effect on buying decision.